A new preload mechanism for a high-speed piezoelectric stack nanopositioner. (June 2016) - Yong, Yuen Kuan
Abstract: Piezoelectric stack actuators are the actuator of choice for many ultra-high precision systems owning to its fast responses and high pushing force capabilities. These actuators are constructed by bonding multiple piezoelectric layers together. An inevitable drawback of these actuators is that there are highly intolerant to tensile and shear forces. During high-speed operations, inertial forces due to effective mass of the system cause the actuators to experience excessive tensile forces. To avoid damage to the actuators, preload must be applied to compensate for these forces. In many nanopositioning systems, flexures are used to provide preload to the piezoelectric stack actuators. However, for high-speed systems with stiff flexures, displacing the flexures and sliding the actuators in place to preload them is a difficult task. One may reduce the stiffness of the flexures to make the preload process more feasible; however, this reduces the mechanical bandwidth of the system. This paper presents a novel preload mechanism that tackles the limitations mentioned above. The preload stage, which is connected in parallel mechanically to a high-speed vertical nanopositioner, allows the piezoelectric stack actuator to be installed and preloaded easily without significantly trading of the stiffness and speed of the nanopositioning system. The proposed vertical nanopositioner has a travel range of 10.6  μ  m. Its first resonant mode appears at about 24 kHz along the actuation direction.